International Collaborative Study on the Assay of Commercially Available High and Low Molecular Weight Urokinases - Gaffney, P J; Tydeman, S M; Kirkwood, T B L; Aronson, D; Murano, G (Thrombosis and Haemostasis, 1981)
Urokinases of different molecular weights are now commercially available. An international collaborative study (eight laboratories) has been conducted to investigate the effect of type and concentration of plasminogen on the assay of two different urokinase preparations against the International Reference Preparation (IRP). Considerable inter-laboratory variation in relative potency estimation was found, and a small effect of plasminogen concentration, independent of type, was apparent.
Keywords: Assay; Urokinases; High and low-molecular weight